Fa’a Sāmoa Criminology: An Aspect of Pacific Criminology Counternarrative - Moses Faleolo; Naomi Fuamatu (International Journal for Crime, Justice and Social Democracy, 2024)
Criminological imagination requires that criminologists adopt multiple perspectives on their study subjects, shifting backwards and forwards between the personal and remote, the micro and the macro, or the theoretical and the empirical. Criminology should thus be ‘refractive’ (Frauley 2015: 21), harnessing the multi-perspectivism of social life to produce fuller, sharper analyses that reveal links between individual lives, social structures, and historical context. One such perspective is fa’a Sāmoa criminology. Not much is known about this worldview or its relationship with criminology, let alone its application as a credible epistemology. This article argues that Western criminology is not the only way to generate new knowledge and recommended solutions and that instead fa’a Sāmoa criminology offers an alternative way. Two qualitative case studies demonstrate how Sāmoan thinking and doing applies in the contexts of Sāmoan young people’s interaction with the youth justice system and hard-to-reach gang-involved Sāmoan peoples. Key implications are highlighted and recommended.